Variability of the Center of Mass in Trained Triathletes in Running After Cycling: A Preliminary Study Conducted in a Real-Life Setting - Evans, Stuart A.; James, Daniel; Rowlands, David; Lee, James B. (Frontiers in Sports and Active Living, 2022)
While the sport of short-distance (Sprint) triathlon provides an opportunity to research the effect of the center of mass (CoM) when cycling and running, much remains to be done. The literature has failed to consistently or adequately report how changes to hand position influence subsequent running as inferred by the magnitude of CoM acceleration. The demands of cycle training in a drops and aerodynamic position followed by running remain unquantified in Sprint Distance triathlon. Thus, far data collected indicate that the cycle to run transition (T2) is important for overall race success. While many age-groupers participate in Sprint Distance triathlon, the lack of T2 based research make comparisons between cycle hand position and ensuing running difficult. The motion of the human body when cycling and running in triathlon can be described by the motion of its CoM in a local coordinate system. Unobtrusive wearable sensors have proven to be an informative resource to monitor the magnitude of CoM accelerations in running. However, the extent to which they are used in cycling is unclear. Therefore, the aim of the present study was to analyse the temporal magnitudes of CoM acceleration when cycling position and cadence is changed and to analyse these effects on running after cycling. Ten recreational triathletes completed two 20 km cycling trials at varied cadence in a drops position (parts of the handlebars that curve outward, CycleDrops) and an aerodynamic position (arms bent, forearms parallel to the ground, CycleAero) immediately followed by a 5 km run at self-selected pace. Torso kinematics by way of CoM acceleration magnitude were captured in a typical training setting using a triaxial accelerometer. CoM acceleration was quantified in m/s2 and variability was measured by the coefficient of variation (CV) and root mean square (RMS). Results from CycleAero indicated that acceleration of the CoM in longitudinal (CV = 1%) and mediolateral directions (CV = 3%) was significantly reduced (p < 0.001) compared to CycleDrops. As for rate of perceived exertion (RPE), a significant difference was observed with triathletes reporting higher values in CycleAero alongside a greater CoM acceleration magnitude in the anteroposterior direction. The CoM varied significantly from RunAero with less longitudinal (CV = 0.2, p < 0.001) and mediolateral acceleration observed (CV = 7.5%, p < 0.001) compared to RunDrops. Although greater longitudinal acceleration was observed in the initial 1 km epoch of RunAero, triathletes then seemingly adjusted their CoM trajectory to record lower magnitudes until completion of the 5 km run, completing the run quicker compared to RunDrops (22.56 min1 ± 0.2, 23.34 min1 ± 0.5, p < 0.001, CV = 1.3%). Coaches may look to use triaxial accelerometers to monitor performance in both cycling and running after cycling.